If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + 6 = 8x + -3 Reorder the terms: 6 + -1x = 8x + -3 Reorder the terms: 6 + -1x = -3 + 8x Solving 6 + -1x = -3 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 6 + -1x + -8x = -3 + 8x + -8x Combine like terms: -1x + -8x = -9x 6 + -9x = -3 + 8x + -8x Combine like terms: 8x + -8x = 0 6 + -9x = -3 + 0 6 + -9x = -3 Add '-6' to each side of the equation. 6 + -6 + -9x = -3 + -6 Combine like terms: 6 + -6 = 0 0 + -9x = -3 + -6 -9x = -3 + -6 Combine like terms: -3 + -6 = -9 -9x = -9 Divide each side by '-9'. x = 1 Simplifying x = 1
| -x-25=-6+30 | | -108=-6n-3(-8n+6) | | -0.10(19)+0.45=0.05(x-6) | | 6(c-7)=-18 | | -15(2x-7)+24=89 | | 3y+4=5y+6 | | 7.7(x-4)=-0.3x+25.2 | | 5[2(3x-3)-4(2x-3)]=3x+17 | | 90=2l+2w | | 4(x-5)+6=2(x-5) | | 5(2x-3)=2(x-2)+5 | | 2X^2-11X-6=0 | | 10y-13=3y+8 | | -3z=12 | | 7(4x+6)=-126 | | 2x*2+21x-11=0 | | f=3x^2-26x+48 | | 8n+5=6n-3 | | 3a+4-a+2=10 | | g(x)=7x-14 | | 6+7y=48 | | .8333333333+.2x=.666666667 | | 13+11x=68 | | 2x+9x=11x | | 6x^2-16x+7=0 | | -4.3=0.7-5y | | 6x-2=3(x+1)+1 | | 4x-90=-6x+40 | | 4n^2-17n+4= | | 2d-7=11d+26 | | 8x+16=9x+9 | | C(m)=0.15m+0.95 |